Working time and digital transition: A complex and ambiguous relationship - Rebelo, G.; Simões, E.; Salavisa, I. (Proceedings of the European Conference on the Impact of Artificial Intelligence and Robotics, ECIAIR 2020, 2020)
The digital transition underway combines different types of technology: digital, physical and biological. These three families of technologies interact, drawing on the progress in artificial intelligence and machine learning, and creating the opportunity of digitalizing all stages of production and services systems. The increase of digital work represents a deep transformation of economy and society, posing huge challenges to companies, employees and policy makers, and therefore to social scientists. In this context, in European countries, working time regulation has become central to employment policies. The guiding principles of working time management are based on three aspects: the conventional definition of working time flexibility; the development of public measures that aim at making the reduction of working hours advantageous; and the adequacy of working time management to the whole of working life. Advances in information and communication technologies that bring high convenience to personal life are also blurring the lines of work-time and personal time, threatening work-life balance. This situation is raising not only important legal issues, but also ethical considerations related to mandatory or unpaid overtime, and the possibility of employer subtle or explicit coercion. Additionally, the ethicality of unconventional shift work and long work-hour schedules is also at stake in issues like the gender-based inequities related to working hours, and employers' responsibilities for protecting individuals who are not employees from the indirect effects of demanding work schedules, namely affecting the work-family balance. In terms of research methods, after an assessment of the transformations underway, based on literature review and documentary analysis, we will develop a qualitative approach with semi-structured interviews, which will allow to analyse the position of different key actors (employers' and trade union confederations) on long working hours and their effects.